2018
DOI: 10.3389/fphar.2018.01299
|View full text |Cite
|
Sign up to set email alerts
|

Strong Inhibitory Effect, Low Cytotoxicity and High Plasma Stability of Steroidal Inhibitors of N-Methyl-D-Aspartate Receptors With C-3 Amide Structural Motif

Abstract: Herein, we report the synthesis, structure-activity relationship study, and biological evaluation of neurosteroid inhibitors of N-methyl-D-aspartate receptors (NMDARs) receptors that employ an amide structural motif, relative to pregnanolone glutamate (PAG) – a compound with neuroprotective properties. All compounds were found to be more potent NMDAR inhibitors (IC50 values varying from 1.4 to 21.7 μM) than PAG (IC50 = 51.7 μM). Selected compound 6 was evaluated for its NMDAR subtype selectivity and its abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…ECS contained (in mM) 160 NaCl, 2.5 KCl, 10 HEPES, 10 glucose, 2 CaCl 2 , 1 MgCl 2 , and 0.03 glycine (pH‐adjusted to 7.3 with NaOH). Compound stock solutions were prepared fresh before each experiment, and measurements were performed at room temperature (21°C–25°C) (Adla et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ECS contained (in mM) 160 NaCl, 2.5 KCl, 10 HEPES, 10 glucose, 2 CaCl 2 , 1 MgCl 2 , and 0.03 glycine (pH‐adjusted to 7.3 with NaOH). Compound stock solutions were prepared fresh before each experiment, and measurements were performed at room temperature (21°C–25°C) (Adla et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Cells were dissociated in papain, washed, and plated in a Neurobasal A medium supplemented with B27 (Gibco) at a density of 50,000 cellsÁcm À2 on top of a confluent layer of cortical astrocytes grown on collagen/poly-D-lysine-covered glass coverslips. (Adla et al, 2018).…”
Section: Primary Hippocampal Neuronsmentioning
confidence: 99%
“…Cellular uptake of synthetic neurosteroids 1 – 11 (syntheses have been reported in our earlier publications [ 32 , 33 ]) was evaluated by using the MCF-7 (human breast adenocarcinoma; Michigan Cancer Foundation-7) cell line, which is known to express several OATPs and efflux transporters [ 34 , 35 ]. More detailed transport mechanisms were investigated by performing Eadie-Hofstee plot analysis, which revealed that almost all synthesized neurosteroids 1–11 had two distinct transport mechanisms.…”
Section: Resultsmentioning
confidence: 99%